(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The apelin receptor (nomenclature as agreed by the NC-IUPHAR Subcommittee on the apelin receptor [68]) responds to apelin, a 36 amino-acid peptide derived initially from bovine stomach. apelin-36, apelin-13 and [Pyr1]apelin-13 are the predominant endogenous ligands which are cleaved from a 77 amino-acid precursor peptide (APLN, Q9ULZ1) by a so far unidentified enzymatic pathway [80]. A second family of peptides discovered independently and named Elabela [11] or Toddler, that has little sequence similarity to apelin, is present, and functional at the apelin receptor in the adult cardiovascular system [87, 67]. Structure-activity relationship Elabela analogues have been described [61].